Utilização de fontes energéticas alternativas na dieta de vaca em lactação - Paladini, Simoni (2014)
In ruminants feeding alternative foods have been used but for other species these foods would be considered of low nutritional level because of the ability for ruminal fermentation of ruminant animals in substitution of grains, specially corn that is used to human intake and monogastrics at all. With the aim of evaluating the use of some alternative foods in diet of lactating cows the study was accomplished to determine the best food as alternative energy source, and for this the intake and digestibility of dry matter and nutrients, yield and composition of milk, blood glucose levels were analyzed in two collection schedules, and performed evaluation of cost variation and revenue from milk production. For that, five Holstein cows were used in latin square design (5X5) receiving diets containing approximately 16% crude protein in dry matter with different energy sources: protected fat (PF), ground corn grain (GCG), corn crumbled with straw (CCWS), soybean hulls (SBH) and dry cassava starch extraction residue (DCSER). As for DM intake and nutrient there was difference (P<0.05) between diets only for intake of ether extract (EE), neutral detergent fiber (NDF), indigestible acid detergent fiber (iADF) and total digestible nutrients (TDN). For apparent digestibility of dry matter (DMD) and of nutrients and TDN there was difference for all variables. Diets had no effect on body weight, milk production and composition. There was difference in the levels of blood glucose in both harvest schedules, fasting period and six hours after feeding. In economic evaluation the highest rate of profitability was obtained with diets containing soybean hulls and corn crumbled with straw. Alternative food CCWS, SBH and DCSER can be used to feed dairy cows to replace ground corn grain since the cost of these foods are competitive with corn cost